Do Human Resource Practices Enhance Organizational Commitment in SMEs with Low Employee Satisfaction?. (9th February 2012) - Saridakis, George; Muñoz Torres, Rebeca; Johnstone, Stewart
Abstract : This paper considers a large matched employee–employer data set to estimate a model of organizational commitment. In particular, it focuses on the role of firm size and management formality to explain organizational commitment in British small and medium‐sized enterprises (SMEs) with high and low levels of employee satisfaction. It is shown that size 'in itself' can explain differences in organizational commitment, and that organizational commitment tends to be higher in organizations with high employee satisfaction compared with organizations of similar size with low employee satisfaction. Crucially, the results suggest that formal human resource (HR) practices can be used as important tools to increase commitment and thus, potentially, effort and performance within underperforming SMEs with low employee satisfaction. However, formal HR practices commonly used by large firms may be unnecessary in SMEs which benefit from high employee satisfaction and positive employment relations within a context of informality.